Programmed cell death 1 inhibitor alone or combined with chemotherapy for patients with locally advanced or metastatic urothelial carcinoma: a single-center experience - Xing Huang; Chupeng Sun; Peng Zhang; Lei Wang (BMC Urology)
Abstract Background Immune checkpoint inhibitors (ICIs) alone or in combination with standard chemotherapy for advanced urothelial carcinoma (UC) have been tested as first-line treatment in clinical trials. This study aimed to evaluate the clinical outcomes of programmed cell death 1 (PD-1) inhibitor alone or combined with chemotherapy for patients with locally advanced or metastatic UC in a real world clinical care setting, and sought to identify prognostic factors for overall survival (OS). Methods A retrospective, real-world study involving 35 locally advanced or metastatic UC patients treated with PD-1 inhibitor alone or in combination with chemotherapy was conducted. Kaplan–Meier curves were used to assess progression-free survival (PFS) and OS. A Cox regression analysis was conducted to explore the association of baseline variables with OS. Results In our cohort of 35 patients, 7 patients were treated with PD-1 inhibitor alone and 28 with PD-1 inhibitor plus platinum-based chemotherapy. The median OS was 16.0 months (95% CI: 11.9–20.1), and median PFS was 12.0 months (95% CI: 8.6–15.4) for all patients. PD-1 inhibitor combined with chemotherapy was associated with better PFS than PD-1 inhibitor monotherapy (HR: 0.19, p = 0.018). Treatment-related adverse events (AEs) of any grade occurred in 5 (71.4%) patients who received PD-1 inhibitor and 24 (85.7%) patients who received PD-1 inhibitor plus chemotherapy. Eastern Cooperative Oncology Group (ECOG) performance status (PS) and neutrophil-lymphocyte ratio (NLR) were identified as prognostic factors. Conclusion This study suggested that patients with locally advanced or metastatic UC could benefit from PD-1 inhibitor alone or combined with chemotherapy in daily clinical practice. ECOG PS and NLR can be used for prognostication of survival.